Development and design of microstructure based coated electrode for ballistic performance of shielded metal arc welded armour steel joints. (5th August 2016) - Pramanick, A.K.; Das, H.; Reddy, G.M.; Ghosh, M.; Das, G.; Nandy, S.; Pal, T.K.
Abstract: Joining of high strength armour steel plate developed for lighter armour vehicles using both austenitic and ferritic type of electrode/filler wire could show inferior ballistic performance of the welds. Combination of hard facing electrode and softer Austenitic Stainless Steel electrodes, though provided improved ballistic performance, might not satisfy main design criteria such as strength and toughness due to non-homogeneous microstructure of weld metal. In order to satisfy improved ballistic performance as well as other design parameters, it is highly desirable to develop coated electrode which will attribute more homogeneous microstructure in weld metal similar to high strength armour steel plate. The present investigation has attempted to obtain martensite, bainite and some amount of retained austenite in the weld metal by proper design of alloying elements in the coating of SMAW electrode based on metallurgical index. Three different electrodes attributing different combination of microstructural constituents in armour steel weld metals exhibited excellent ballistic performance combined with other design criteria such as strength and toughness at − 40°C. However, among the different microstructural constituents lower bainite along with retained austenite showing maximum toughness both at room temperature and at − 40°C could be considered as most desirable microstructure in armour steel weld metal. Graphical abstract: Highlights: Development of flux formulation for shielded metal arc welding coated electrode. Developed electrodes show excellent ballistic performance of armour steel weldment. Both bainite and martensite with retained austenite show excellent ballistic property. Lower bainite could be considered desirable microstructure to satisfy all the design criteria.